Pengaruh Metode Pembelajaran Problem Solving Terhadap Higher Order Thingking Skill (HOTS) pada Siswa SMP - Rasmuin Rasmuin; Salmin Syah (Jurnal Akademik Pendidikan Matematika, 2021)
Objective of the research was to see the effect of applying Problem Solving method toward students’ Higher Order Thingking Skill (HOTS) at SMP Negeri 2 Kaledupa. The research used quantitative approach with quasi experimental design. Population in the research was all grade VII SMP Negeri 2 Kaledupa consisted of three classes were A, B, and C with 60 students in academic year 2020/2021. Samples taken consisted of 2 classes by using simple random sampling technique in which class VII B consisted of 20 students as experimental class and class VII C consisted of 20 students as control class. Instrument used in this research was HOTS essay test. Research outcome showed that: 1) the mean score of pretest result in experimental class was 20.40; 2) the mean score of posttest result in experimental class was 37.950; 3) the mean score of pretest result in control class was 19.10; 4) the mean score of posttest result in control class was 29.30. Based on the Higher Order Thingking Skill (HOTS) and the result of inferential analysis used t-test showed that applying Problem Solving learning method significantly effected toward students’ Higher Order Thingking Skill (HOTS) at SMP Negeri 2 Kaledupa.